1972
DOI: 10.1029/ja077i004p00720
|View full text |Cite
|
Sign up to set email alerts
|

Spectral measurements of noctilucent clouds

Abstract: The first high‐resolution, absolutely calibrated spectral intensity measurements of noctilucent clouds were made on the night of July 22–23, 1969, from Fort Nelson, British Columbia, with a scanning spectrophotometer. These spectra have no discernible emission or absorption features attributable to NLC. The measured radiance of a bright band in the moderately bright display was about 6 kR/A at 4800 A, the wavelength of maximum radiance. If the clouds are regarded as a monodisperse aerosol of 1300‐A radius ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…For example, Witt [1960] inferred sizes of ∼130 nm from a ground‐based polarimeter operating at visible wavelengths. For many years the accepted standard spectrum [ Fogle and Rees , 1972] has shown that NLC light was primarily scattered sunlight and suggested a scatterer size (∼100 nm) comparable to that found from polarization measurements. However, these visible light measurements suffered from ground albedo effects common at visible wavelengths as well as from effects of atmospheric extinction and other background problems.…”
Section: Introductionmentioning
confidence: 86%
“…For example, Witt [1960] inferred sizes of ∼130 nm from a ground‐based polarimeter operating at visible wavelengths. For many years the accepted standard spectrum [ Fogle and Rees , 1972] has shown that NLC light was primarily scattered sunlight and suggested a scatterer size (∼100 nm) comparable to that found from polarization measurements. However, these visible light measurements suffered from ground albedo effects common at visible wavelengths as well as from effects of atmospheric extinction and other background problems.…”
Section: Introductionmentioning
confidence: 86%
“…Polar mesospheric clouds (PMC) were discovered by satellite [ Donahue et al , 1972] and are now considered to be the poleward extension of noctilucent clouds (NLC) observed from the ground for decades. Ground observations at low polar latitudes employ traditional optical methods including cameras [ Fritts et al , 1993; Warren et al , 1997], spectrometers and spectrographs [ Fogle and Rees , 1972; Hecht et al , 1997] and polarizers [ Witt , 1960]. These traditional observations have established the whispy nature of the clouds and their small‐scale, local structure [ Fritts et al , 1993].…”
Section: Introductionmentioning
confidence: 99%